Re-evaluating the identity of Passiflora hastifolia (Passifloraceae), resulting into a new species of Passiflora ser. Menispermifoliae (Passifloraceae) from North-Central Peru - Kuethe, J.r. (Phytotaxa, 2025)
In 2009, a plant species from Tarapoto, Peru, was introduced into cultivation and identified as Passiflora hastifolia. However, a subsequent expedition to Bolivia, which included a visit to the type location of P. hastifolia, prompted a re-evaluation of the source material. This investigation revealed that the Peruvian material was incorrectly identified, leading to the recognition of a new species which is here described as Passiflora asprantha. The study provides a detailed comparison between P. hastifolia from Bolivia and the previously misidentified specimens circulating in popular cultivation under that name. Key differences in morphology, such as the acute apices of the leaf for P. hastifolia versus the ovoid apices in the Peruvian accessions; and flower structure which is pink-purple in P. hastifolia but fully white in the new species, are highlighted. Additionally, this paper includes notes on the ecology and distribution of the newly instated Passiflora asprantha, noting its specific habitat preferences and geographical range. This discovery contributes to the understanding of biodiversity within the Passiflora genus and underscores the importance of accurate species identification in botanical research.